Preserving Traditional Knowledge of Prospective Biology Teachers through Science Integrated Learning with Next-Generation Science Standards - Sukmawati, Ika; Widiyatmoko, Arif; Tawang, Alene; Muhlisin, Ahmad (Jurnal Pendidikan IPA Indonesia, 2024)
This study aims to find the relationship between prospective biology teachers' ethnicity and teaching skills to preserve indigenous knowledge in Indonesia. The research intervention integrates the Science Integrated Learning (SIL) model with NGSS dimensions in the teaching practices of prospective biology teachers. The method chosen was embedded experimental with a quasi-experimental design consisting of three stages: a qualitative stage before, a qualitative stage during, and a qualitative stage after the intervention. The research targets were 60 prospective science teachers in two different cluster universities, each with 30 prospective teachers. Interpretation of quantitative and qualitative data in the form of statistical test results. The analysis of the comparison test using the t-statistic model obtained a difference in the average score of microteaching practice of 0.3, with an average of the first practice of 2,613 with a standard deviation of 0.3024 and the second practice of 2,921 with a standard deviation of 0.3122. The second microteaching practice experienced an increase in scores from the first practice. The study concluded that prospective biology teachers' skills in preserving indigenous Indonesian traditional knowledge can be realized through the SIL Model integrated with NGSS.  The research results allow prospective teachers to utilize students' experiences as learning sources and hopefully can contribute on the development of prospective teacher education policies oriented toward preserving Indigenous knowledge in Indonesia.